2021
DOI: 10.3389/fcimb.2021.607422
|View full text |Cite
|
Sign up to set email alerts
|

The Hypothetical Inclusion Membrane Protein CPSIT_0846 Regulates Mitochondrial-Mediated Host Cell Apoptosis via the ERK/JNK Signaling Pathway

Abstract: Chlamydia psittaci is an important zoonotic factor associated with human and animal atypical pneumonia. Resisting host cell apoptosis is central to sustaining Chlamydia infection in vivo. Chlamydia can secrete inclusion membrane proteins (Incs) that play important roles in their development cycle and pathogenesis. CPSIT_0846 is an Inc protein in C. psittaci identified by our team in previous work. In the current study, we investigated the regulatory role of CPSIT_0846 in HeLa cell apoptosis, and explored poten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 60 publications
0
1
0
Order By: Relevance
“…In our study, it was found by JC-1 assay that depolarization of MMP increased with increasing BbF concentration compared to control, especially in BEAS-2B cells. The decrease in MMP would lead to the opening of the mitochondrial permeability transition pore in the mitochondrial membrane, the release of Cyt C into the cytoplasm, and the subsequent activation of caspase-9, ultimately leading to apoptosis (Tang et al, 2021). Apoptosis is also regulated by other proteins.…”
Section: Bbf Interferes With the Expression Of Proteins Of Mitochondr...mentioning
confidence: 99%
“…In our study, it was found by JC-1 assay that depolarization of MMP increased with increasing BbF concentration compared to control, especially in BEAS-2B cells. The decrease in MMP would lead to the opening of the mitochondrial permeability transition pore in the mitochondrial membrane, the release of Cyt C into the cytoplasm, and the subsequent activation of caspase-9, ultimately leading to apoptosis (Tang et al, 2021). Apoptosis is also regulated by other proteins.…”
Section: Bbf Interferes With the Expression Of Proteins Of Mitochondr...mentioning
confidence: 99%